Strategi Pemasaran Digital dalam Pengembangan Agrowisata Kisuci di Desa Cipambuan, Babakan Madang, Bogor - Sari Sakti, Essy Malays; Marhalinda; Supradaka; Prabowo, Hayu S. (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Cipambuan Village is one of the villages in the Sentul circle and has the potential to be developedinto an agrotourism village. Currently the village is managed by the Kisuci community, which is acommunity that focuses on environmental issues, especially on preserving the Cikeas River,mitigating climate change, raising public awareness in managing natural resources sustainablywith the hope of improving the welfare of the surrounding community through the ecotourismsector. The development of Kisuci ecotourism is not progressing quickly, this is because the Kisucitourist destination is not yet widely known by tourists and prospective tourists. This research aimsto examine the facilities owned by the Kisuci tourist destination so that they can be promotedthrough digital marketing. The research method used is qualitative with a descriptive approach,data collection techniques are observation, interviews and literature review. The findings showedthat the management had not used digital marketing strategies, did not have tours for children anddid not have program packages that could be sold to schools. The recommended marketingstrategy is a strategy through digital marketing on social media advertising, promotional content and viral marketing using endorsements. It is hoped that the recommended strategy can beimplemented to increase tourists visiting the Kisuci tourist destination